AN EMPERICAL STUDY ON STUDENT HAPPINESS IN PUBLIC HIGHER UNIVERSITY AMONG STUDENTS UITM KOTA BHARU - Ab Rahman , Siti Maziah; Hamizi, Hafzi Aizzat; Hazana , Muhammad Aliff Firman; Wan Nawang , Wan Muhammad Arif Syahmi; Mohd Zaki , Adeeba Najihah; Shaari, Rustam (Journal of Islamic, Social, Economics and Development, 2024)
Happiness is currently one of the primary indicators of social progress in modern society, particularly among students at higher learning institutions. The study examines the relationship between family factors, lifestyles, social and motivation, with happiness index. The issue of happiness in students has been debated among academician’s f practitioners, and policy makers nowadays. This is because the concept of happiness is very likely to help guide progress towards sustainable development. Whereas sustainable development entails all parties especially public and private students to balance society, social and environmental objectives in a holistic manner. When students pursue society wealth in a lopsided manner, overriding social and environmental objectives, the results often negatively impact human wellbeing inside and outside students such as employees, customers and communities. Therefore, there is a strong need for students to ensure the sustainability of their development by understanding the level of happiness of their feeling. However, evaluating happiness could be inconclusive since available measurements were one-dimensional and non-academically validated. Hence, the objective of this study is to propose a systematic measurement of student happiness index that is conceptualized using 3-dimensional Authentic Happiness theory which to be operationalized in service industries settings as these industries employ substantial number of human resources. This study also aims to quantitatively produce the index for each participating service student besides analyzing the identified research framework using structural equation modeling, where studies emphasizing such an approach are relatively scarce.